Communities of Practice in Peer Review: Outlining a Group Review Process. (October 2019) - Nagler, Alisa; Ovitsh, Robin; Dumenco, Luba; Whicker, Shari; Engle, Deborah L.; Goodell, Kristen
Abstract : Traditional peer review remains the gold standard for assessing the merit of scientific scholarship for publication. Challenges to this model include reliance on volunteer contributions of individuals with self-reported expertise; lack of sufficient mentoring and training of new reviewers; and the isolated, noncollaborative nature of individual reviewer processes. The authors participated in an Association of American Medical Colleges peer-review workshop in November 2015 and were intrigued by the process of group peer review. Subsequent discussions led to shared excitement about exploring this model further. The authors worked with the staff and editors of Academic Medicine to perform a group review of 4 submitted manuscripts, documenting their iterative process and analysis of outcomes, to define an optimal approach to performing group peer review. Individual recommendations for each manuscript changed as a result of the group review process. The group process led to more comprehensive reviews than each individual reviewer would have submitted independently. The time spent on group reviews decreased as the process became more refined. Recommendations aligned with journal editor findings. Shared operating principles were identified, as well as clear benefits of group peer review for reviewers, authors, and journal editors. The authors plan to continue to refine and codify an effective process for group peer review. They also aim to more formally evaluate the model, with inclusion of feedback from journal editors and authors, and to compare feedback from group peer reviews versus individual reviewer feedback. Finally, models for expansion of the group-peer-review process are proposed.